Determinants of Sustainable Tourism Development in Buon Ma Thuot, Vietnam - Minh, Nguyen Ngoc (Journal of Posthumanism, 2025)
Sustainable tourism development is an essential requirement for tourist destinations in the current period. Many factors influence the sustainable development of a destination, such as resources, human capital, infrastructure, and more. In this article, the author analyzes the impact of several factors on the sustainable tourism development of Buon Ma Thuot. The research was conducted using sociological survey methods, with 673 valid responses included in the analysis. The results show that all eight proposed factors have a positive impact on the sustainable tourism development of Buon Ma Thuot.